Provenance and Annotation of Data and Processes: 5th International Provenance and Annotation Workshop, IPAW 2014, Cologne, Germany, June 9-13, 2014. Revised Selected Papers - Ludäscher, Bertram; Plale, Beth (LNCS sublibrary. SL 3, Information systems and applications, incl. Internet/Web and HCI, 2015)
This book constitutes the revised selected papers of the 5th International Provenance and Annotation Workshop, IPAW 2014, held in Cologne, Germany in June 2014. The 14 long papers, 20 short papers and 4 extended abstracts presented were carefully reviewed and selected from 53 submissions. The papers include tools that enable provenance capture from software compilers, from web publications and from scripts, using existing audit logs and employing both static and dynamic instrumentation.